Associations between food-specific IgG antibodies and intestinal permeability biomarkers - Vita, Alexandra Adorno; Zwickey, Heather; Bradley, Ryan (Frontiers in Nutrition, 2022)
Increasing translational evidence suggests that intestinal permeability may be a contributing factor to systemic inflammatory events and numerous pathologies. While associations between IgE-mediated food allergies and increased intestinal permeability have been well characterized, the relationship between IgG-mediated food sensitivities and intestinal permeability is not well described in the literature. Thus, we tested for associations between intestinal permeability biomarkers and food-specific IgG antibodies in 114 adults, with and without gastrointestinal symptoms. The intestinal permeability biomarkers anti-lipopolysaccharide (LPS) and anti-occludin IgG and IgA, but not anti-vinculin or anti-CdtB IgG, were significantly and positively associated with IgG-mediated food sensitivities. These significant relationships were attenuated by adjusting for the severity of wheat, dairy, and egg reactions. The results of this study support strong associations between titers of food-specific IgG antibodies and intestinal permeability biomarkers in adults, to the extent that the presence of multiple IgG antibodies to food, and increasing IgG food titers, can be considered indicative of increased antibodies to LPS and occludin. Notably, neither IgG titers to wheat, eggs, and dairy, nor permeability biomarkers, were increased in symptomatic participants compared to those without symptoms.